Peran Psikologi Tasawuf dalam Membangun Kesehatan Mental di Era Modern - Allya Zulfani, Hanum; Salsabilah, Elsha (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Mental health has become a crucial issue in modern life, marked by social pressures, crises of meaning, and increasing psychological disorders. In this context, Sufistic psychology emerges as a spiritual approach capable of addressing the inner needs of modern humans. Sufism emphasizes soul purification, self-control, and closeness to God as a foundation for achieving inner peace. Through practices such as dhikr (remembrance of God), muhasabah (self-reflection), tafakkur (contemplation), and tawakal (trust in God), Sufism serves as an effective spiritual coping mechanism for managing stress and strengthening psychological resilience. This study uses a descriptive qualitative approach with a library research method to examine the role of Sufistic psychology in building mental health. The findings indicate that Sufistic psychology is not only curative but also preventive and transformative. However, its implementation still faces challenges, including mystical stigmas, low spiritual literacy, and clashes between traditional and modern values. Therefore, an integrative and contextual approach is needed so that Sufistic values can make a real contribution to improving mental health in contemporary society.